The Impact of Covid-19 on Student Achievement in Higher Education - Arif Hidajad; Woolnough Cale; Bouyea Jonathan (Yayasan Adra Karima Hubbi, 2024)
Background. The Covid-19 pandemic has a huge impact on various fields, especially in the world of education. Learning that was originally carried out face-to-face becomes learning that is carried out online or online. Purpose. Online learning has been approved by the government because it is one of the solutions to overcome the spread of the covid-19 virus. The purpose of this study is to be able to test the hypothesis regarding the impact of covid-19 on student achievement. Method. The method used in this research is quantitative method, the data obtained through distributing questionnaires by utilising google from. Results. he results of this study indicate that lectures conducted online during covid-19 have a huge impact on the achievements obtained by students. Conclusion. The conclusion of the study shows that there is a significant relationship between learning conducted online during the covid-19 pandemic and the learning achievements obtained by students.